2021
DOI: 10.1186/s41938-020-00357-3
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi, Beauveria bassiana and Metarhizium anisopliae, confer control of the fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), in two tomato varieties

Abstract: Background The fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), is an important pest of tomatoes that reduces yield and fruit quality resulting in losses of up to 100%. The pest has developed resistance to chemical insecticides, therefore necessitating alternative control measures. The entomopathogenic fungi (EPF) Beauveria bassiana and Metarhizium anisopliae have been exploited extensively for biological control of the insect pests of economic importance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
2
21
0
2
Order By: Relevance
“…The weak positive relationship between endophytic M. robertsii presence and relative growth rate of FAW was inconsistent with similar studies that demonstrated negative effects of endophytic Metarhizium spp. on plant-feeding insects [38,41,57,58]. In our previous study, the relative growth rate of larvae of another noctuid species, black cutworm (Agrotis ipsilon), was lower after feeding on leaf tissue from M. robertsii-inoculated maize compared with the relative growth rate of black cutworm feeding on control leaf tissue, and unaffected by colonization intensity [27].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The weak positive relationship between endophytic M. robertsii presence and relative growth rate of FAW was inconsistent with similar studies that demonstrated negative effects of endophytic Metarhizium spp. on plant-feeding insects [38,41,57,58]. In our previous study, the relative growth rate of larvae of another noctuid species, black cutworm (Agrotis ipsilon), was lower after feeding on leaf tissue from M. robertsii-inoculated maize compared with the relative growth rate of black cutworm feeding on control leaf tissue, and unaffected by colonization intensity [27].…”
Section: Discussionmentioning
confidence: 91%
“…Colonized maize tissue may also have had defensive metabolites that were ineffective against FAW owing to the deactivation of metabolites in their midguts via antimicrobial peptides and high alkalinity, and the rapid evacuation of harmful metabolites from their bodies [27,[64][65][66]. Plant defense interactions vary depending on which plant cultivar, herbivore species, and endophytic isolate is used in experiments [2,22,36,39,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cendawan B. bassiana selain sebagai agens pengendalian hama juga bersifat endofit yang hidup di dalam jaringan sehingga dapat melindungi tanaman dari berbagai jenis penyakit penting (Bonnie et al 2010;Castillo-Lopez dan Sword 2015;Greenfield et al 2016;Prabhukarthikeyan et al 2017;Jaber dan Ownley 2018;Mwanburi 2021). Berbagai jenis penyakit tanaman yang dapat dihambat perkembangannya oleh cendawan B. bassiana yaitu penyakit tular tanah (soil born disease) antara lain: Botrytis cinerea, Verticillium dahliae, Phytophthora megapserma, dan beberapa penyakit tular tanah lainnya pada berbagai jenis tanaman pangan, perkebunan maupun hortikultura (Akello et al 2007;Ownley et al 2008;Powell et al 2009;Tefera dan Vidal 2009;Punja et al 2016;Lozano-Tovar et al 2017;Saragih et al 2019;Barra-Bucarei et al 2020).…”
Section: Cendawan B Bassiana Bersifat Endofitunclassified
“…These microbial insecticides attach to the host cuticle, germinate and penetrate hemolymph, leading to fungal growth inside the host, eventually producing and dispersing secondary infectious conidia [8]. Entomopathogenic fungi, Beauveria bassiana and Metarhizium anisopliae, have shown potential against various pests, including Aedes albopictus [9], Bemisia tabaci [10], Culex pipiens [11] and Spodoptera frugiperda [12]. Insects respond to pathogenic infections by initiating various immune pathways, activating transcription factors, and gene expressional changes [13].…”
Section: Introductionmentioning
confidence: 99%